INOVASI SOSIAL DALAM PENGELOLAAN JAMUR: Membangun Ekonomi Berkelanjutan - Wahyu Nurhayati, Dwi Astuti; Oktavia, Novi Tri (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
Tanjungsari Village, Boyolangu Sub-district, Tulungagung Regency launched an innovative initiative in addressing the economic challenges faced by the community. One of the main activities of this initiative is mushroom processing training. The purpose of this activity is to help the Tanjungsari Village community develop oyster mushroom processing talents by adding mushroom processing innovations by BUMDes Tanjungsari. The target of the mushroom processing activity is people who live in Tanjungsari Village. Mushroom processing training in Tanjungsari Village is a strategic step to overcome economic challenges and build community economic independence. From participating in mushroom product processing training activities, the community gained knowledge, experience, and skills about mushroom processing which were later expected to be applied to independent businesses that helped the participants' economy. With increased knowledge, technical skills, and entrepreneurial spirit, the trainees are able to start a sustainable independent business. The partnership with BUMDes also ensures that the mushroom cultivation products can be marketed well, creating a mutually supportive economic ecosystem. Keywords: Economic, Innovation; Social